Tunable Photoluminescence from Monolayer Molybdenum Disulfide - Brendan F. M. Healy; Sophie L. Pain; James Lloyd‐Hughes; Nicholas E. Grant; John D. Murphy (Advanced Materials Interfaces, 2024)
Abstract Monolayer molybdenum disulfide (1L MoS2), a promising optoelectronic material, emits strong visible photoluminescence (PL). Systematic control of the intensity, energy, and spectral width of PL from 1L MoS2 on silicon dioxide/silicon (SiO2/Si) is demonstrated via simple external treatments. Treating MoS2 with solutions formed from the superacid bis‐(trifluoromethanesulfonyl)amide (TFSA) enhances, blueshifts, and sharpens the PL. Treatments with solutions from structurally analogous chemicals that lack sulfur, in the case of bis(trifluoroacetamide) (BTFA), or lack fluorine, in the case of methanesulfonamide (MSA), show the same trend, suggesting a two‐component mechanism for TFSA involving the presence of electronegative species and sulfur vacancy passivation. Up to ≈100× enhancement of the PL intensity is achieved, with the peak blueshifted by ≈30 meV and the spectral linewidth halved. Conversely, direct thermal atomic layer deposition (ALD) of aluminum oxide (Al2O3) or hafnium oxide (HfO2) is found to suppress the PL by up to a factor of ≈3, redshift by up to ≈70 meV, and broaden by ≈3×. Single‐spot and mapping Raman/PL techniques are combined in a robust characterization process to associate changes in the PL character to charge doping. This work demonstrates the convenient tunability of the optical behavior of 1L MoS2 by varying the electron density.